2018
DOI: 10.1590/1413-812320182312.31012016
|View full text |Cite
|
Sign up to set email alerts
|

Lazer entre universitários da área da saúde: revisão de literatura

Abstract: Resumo Esse artigo objetiva analisar estudos sobre lazer entre universitários da área da saúde, a partir de revisão da literatura. Utilizou-se os descritores: lazer e estudantes, e seus respectivos termos em espanhol e inglês na base de dados Bireme, resultando no final da revisão em 32 artigos. Observou-se um predomínio dos seguintes interesses do lazer: desportivos, sociais, intelectuais e artísticos, com maior número de artigos apresentando vivências nos esportes. Notou-se também que a ingestão de álcool no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 40 publications
(61 reference statements)
0
4
0
3
Order By: Relevance
“…Physical practice activities have been discussed in many of the studies investigating the leisure and extracurricular activities of university youth. It is suggested that this dominance is due to the ease of quantitative measurement of PA in terms of time and intensity and the positive effects of PA on health (31). A study involving 360 medical students determined that 53.9 % of the students participated in extracurricular activities, and participation in extracurricular activities was associated with a low prevalence of burnout, regardless of the chosen activity (32).…”
Section: Discussionmentioning
confidence: 99%
“…Physical practice activities have been discussed in many of the studies investigating the leisure and extracurricular activities of university youth. It is suggested that this dominance is due to the ease of quantitative measurement of PA in terms of time and intensity and the positive effects of PA on health (31). A study involving 360 medical students determined that 53.9 % of the students participated in extracurricular activities, and participation in extracurricular activities was associated with a low prevalence of burnout, regardless of the chosen activity (32).…”
Section: Discussionmentioning
confidence: 99%
“…Literature shows that medical students with higher levels of resilience had better quality of life and better perception of the educational environment 42 , and one of the strongest strategies to stimulate resilience among students is to intensify interpersonal relationships 4,10,32,36,[43][44] . These data were present in our study, showing that 'social relations' have a good/very good rating for 55.6% of students, which is the domain with the best score.…”
Section: Discussionmentioning
confidence: 99%
“…Nesta seara são escassos os investimentos e ações de instituições de ensino superior públicas e privadas, todavia são comuns a proposição e implementação de ações de lazer pelos próprios estudantes. Achados de estudos apontaram uma associação positiva entre a valorização do tempo livre dos estudantes de graduação da área da saúde utilizado com vivências no âmbito do lazer e melhores condições de saúde, potencializando a necessidade de criação de ambientes propícios para tais práticas (Vieira et al, 2018). Neste sentido, releva-se a necessidade de propostas significativas de ações culturais no contexto das instituições públicas e privadas de ensino superior.…”
Section: Corroboramos O Entendimento De Chaves and Silveira De Queunclassified